2007
DOI: 10.1111/j.1365-2842.2006.01720.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of prefabricated post dimensions on restored maxillary central incisors

Abstract: The aim of this study was to test the following hypothesis: biomechanical performance (fracture strength and stress distribution) of restored teeth is less sensitive to post diameter and post length when using glass fibre posts than when using stainless steel posts. First, an experimental fracture strength test was performed on 80 extracted human maxillary central incisors. Teeth were decoronated, treated endodontically and restored (40 with glass fibre posts and 40 with stainless steel posts), and the length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
38
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 25 publications
8
38
0
Order By: Relevance
“…Ferrari et al (Ferrari et al, 2008), on the other hand, concluded that post length does not influence the biomechanics of restored teeth. The same conclusion about the non-significance of the post length was obtained by the authors in a study with in vitro tests and with FEA for both metallic and fibre posts (Rodríguez-Cervantes et al, 2007). More recently Hsu et al (Hsu et al, 2009) concluded that when a metal post is used, the post should be as long as possible, while the biomechanical performance of a glass-fibre post combined with a composite resin core was less sensitive to post length.…”
Section: About the Effect Of Post Lengthsupporting
confidence: 59%
See 4 more Smart Citations
“…Ferrari et al (Ferrari et al, 2008), on the other hand, concluded that post length does not influence the biomechanics of restored teeth. The same conclusion about the non-significance of the post length was obtained by the authors in a study with in vitro tests and with FEA for both metallic and fibre posts (Rodríguez-Cervantes et al, 2007). More recently Hsu et al (Hsu et al, 2009) concluded that when a metal post is used, the post should be as long as possible, while the biomechanical performance of a glass-fibre post combined with a composite resin core was less sensitive to post length.…”
Section: About the Effect Of Post Lengthsupporting
confidence: 59%
“…These first works were twodimensional and were conducted with programs developed by the researchers themselves. Later, the advances in computer resources and in commercial software for FEA extended the use of different commercial programs, allowing more accurate and predictive threedimensional models to be developed Barjau-Escribano et al, 2006;Boschian Pest et al, 2006;Ferrari et al, 2008;Genovese et al, 2005;Gonzalez-Lluch et al, 2009b;Maceri et al, 2009;Rodríguez-Cervantes et al, 2007;Sorrentino et al, 2007). The number of publications dealing with FE simulation in endodontics has increased exponentially in recent years.…”
Section: Historical Overview Of Biomechanical Models For Simulating Ementioning
confidence: 99%
See 3 more Smart Citations